Automation pipeline of the VFP - Fan, Lushun; Kipouros, Timoleon (Cranfield University, 2026)
An automated aerodynamic analysis framework based on a viscous full potential (VFP) solver is developed and applied to a SAAB wing–body configuration. The method combines a compressible full potential formulation with entropy-based artificial viscosity and viscous–inviscid interaction modelling. An end-to-end automation pipeline enables batch execution and post-processing without manual intervention. Eighteen flight conditions were computed in under one hour, achieving reduction in turnaround time. The results capture key aerodynamic trends, including linear lift behaviour, quadratic drag rise, realistic drag polars, and transonic wave-drag effects. While absolute drag levels are slightly optimistic, the framework provides an efficient and practical tool for preliminary aircraft design and early-stage decision-making.